PENERAPAN METODE IPA (IMPORTANCE PERFOMANCE ANALYSIS) UNTUK MENGANALISIS KEPENTINGAN DAN KEPUASAN PENUMPANG TERHADAP KUALITAS PELAYANAN BUS TRANS KOETARADJA (STUDI KASUS : KORIDOR I KEUDAH – DARUSSALAM) - Lia Fajri; Sugiarto Sugiarto; Renni Anggraini (Prodi Magister Teknik Sipil Unsyiah, 2019)
The use of private vehicles that increases continuously due to the poor of public transport services is one of the causes of congestion. To solve this problem, the City Government of Banda Aceh provides Trans Koetaradja Bus. The limitations of existing public transport services in the city of Banda Aceh caused the community to attempt facilitate their own movements with private vehicles. So that the development of Trans Kutaraja is faced with the challenge of how Trans Kutaraja is able to attract private vehicle users who are the majority of road user in the city of Banda Aceh. therefore, it is important to know how the user respondses to the service quality of Trans Kutaraja. This study aims to analyze the quality of Trans Koetaradja Bus services and determine the quality of Trans Koetaradja Bus services of attributes that are prioritized based on the perception of the users of Trans Koetaradja Bus by using the Importance Performance Analysis Method consisting of quadrant analysis and gap analysis. From the results of the quadrant analysis the IPA method for Trans Koetaradja users is more focused on the factors that most influence on the quality of bus services. It can be seen from the indicators located in quadrant I (top priority) consisting of indicators such as the availability of trash can at the bus stop, ease of obtaining information related to the route and time of bus arrival, the accuracy of bus travel schedules, time speed spent on bus trips from one point to another and the time period of arrival between one fleet and another.